2013
DOI: 10.1590/s1982-56762013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Análise de risco da ocorrência de Sigatoka-negra baseada em modelos polinomiais: um estudo de caso

Abstract: RESUMOA Sigatoka-negra (Mycosphaerella fijiensis) ameaça os bananais comerciais em todas as áreas produtoras do mundo e provoca danos quantitativos e qualitativos na produção, acarretando sérios prejuízos financeiros. Faz-se necessário o estudo da vulnerabilidade das plantas em diversos estádios de desenvolvimento e das condições climáticas favoráveis à ocorrência da doença. Objetivou-se com este trabalho desenvolver um modelo probabilístico baseado em funções polinomiais que represente o risco de ocorrência d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, the pieces of filter paper colonized by the fungus mycelium were transferred to cryotubes with silica gel for cryo-preservation at −20 °C. In SPVR-I, the management was based on intensive fungicide sprays, with around 8 to 14 fungicide calendar-based applications per year to control black Sigatoka, mostly because of the extremely predisponent weather conditions for the disease, which includes high humidity (>90%), the presence of leaf wetness and temperatures ranging from 26-28 • C [2,19,[32][33][34]. The Vale do Ribeira region represents the highest banana production both in São Paulo State and Brazil, where the susceptible banana varieties Prata and Nanica predominate [7,19,33].…”
Section: Mycosphaerella Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the pieces of filter paper colonized by the fungus mycelium were transferred to cryotubes with silica gel for cryo-preservation at −20 °C. In SPVR-I, the management was based on intensive fungicide sprays, with around 8 to 14 fungicide calendar-based applications per year to control black Sigatoka, mostly because of the extremely predisponent weather conditions for the disease, which includes high humidity (>90%), the presence of leaf wetness and temperatures ranging from 26-28 • C [2,19,[32][33][34]. The Vale do Ribeira region represents the highest banana production both in São Paulo State and Brazil, where the susceptible banana varieties Prata and Nanica predominate [7,19,33].…”
Section: Mycosphaerella Isolationmentioning
confidence: 99%
“…In SPVR-I, the management was based on intensive fungicide sprays, with around 8 to 14 fungicide calendar-based applications per year to control black Sigatoka, mostly because of the extremely predisponent weather conditions for the disease, which includes high humidity (>90%), the presence of leaf wetness and temperatures ranging from 26-28 • C [2,19,[32][33][34]. The Vale do Ribeira region represents the highest banana production both in São Paulo State and Brazil, where the susceptible banana varieties Prata and Nanica predominate [7,19,33]. In plantations from these susceptible banana varieties under the predominant highly favorable weather conditions in the Vale do Ribeira, the pathogens' incubation period could range from as low as 13 to 14 days, whereas under unfavorable weather the incubation period could be extended up to 35 days [7,19,33,34].…”
Section: Mycosphaerella Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographical distribution and prevalence of the SDC in Brazil follow a humidity cline. For instance, black Sigatoka is considered more prevalent and destructive under conducive weather conditions, which include high humidity (>90%), the presence of leaf wetness, and temperatures ranging from 26-28 • C [8, [14][15][16][17]. In banana plantations where the susceptible and widely cultivated varieties Prata and Nanica [6,18] are used, the incubation period for Mf could be as short as 13 to 14 days, whereas under unfavorable conditions, the pathogen's incubation period could extend to 35 days [4,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, black Sigatoka is considered more prevalent and destructive under conducive weather conditions, which include high humidity (>90%), the presence of leaf wetness, and temperatures ranging from 26-28 • C [8, [14][15][16][17]. In banana plantations where the susceptible and widely cultivated varieties Prata and Nanica [6,18] are used, the incubation period for Mf could be as short as 13 to 14 days, whereas under unfavorable conditions, the pathogen's incubation period could extend to 35 days [4,14,[16][17][18]. For Mm, in planta epidemiological studies under controlled conditions indicated that spores germinate 2-3 h after deposition on banana leaves if a water film is present or if humidity is high [19].…”
Section: Introductionmentioning
confidence: 99%